Synthesis of digital locomotive receiver of automatic locomotive signaling - Goncharov, K. V. (Science and Transport Progress, 2013)
Purpose. Automatic locomotive signaling of continuous type with a numeric coding (ALSN) has several disadvantages: a small number of signal indications, low noise stability, high inertia and low functional flexibility. Search for new and more advanced methods of signal processing for automatic locomotive signaling, synthesis of the noise proof digital locomotive receiver are essential. Methodology. The proposed algorithm of detection and identification locomotive signaling codes is based on the definition of mutual correlations of received oscillation and reference signals. For selecting threshold levels of decision element the following criterion has been formulated: the locomotive receiver should maximum set the correct solution for a given probability of dangerous errors. Findings. It has been found that the random nature of the ALSN signal amplitude does not affect the detection algorithm. However, the distribution law and numeric characteristics of signal amplitude affect the probability of errors, and should be considered when selecting a threshold levels According to obtained algorithm of detection and identification ALSN signals the digital locomotive receiver has been synthesized. It contains band pass filter, peak limiter, normalizing amplifier with automatic gain control circuit, analog to digital converter and digital signal processor. Originality. The ALSN system is improved by the way of the transfer of technical means to modern microelectronic element base, more perfect methods of detection and identification codes of locomotive signaling are applied. Practical value. Use of digital technology in the construction of the locomotive receiver ALSN will expand its functionality, will increase the noise immunity and operation stability of the locomotive signal system in conditions of various destabilizing factors.